Inclusive Education in the United States - Tanner, C. Kenneth; Linscott, Deborah Jan Vaughn; Galis, Susan Allan (Education Policy Analysis Archives, 1996)
School reform issues addressing inclusive education were investigated in this nationwide (United States) study. A total of 714 randomly selected middle school principals and teachers responded to concerns about inclusion, "degree of change needed in" and "importance of" collaborative strategies of teaching, perceived barriers to inclusion, and supportive activities and concepts for inclusive education. There was disagreement among teachers and principals regarding some aspects of inclusive education and collaborative strategies. For example, principals and special education teachers were more positive about inclusive education than regular education teachers. Collaboration as an instructional strategy for "included" students was viewed as a high priority item. Responders who had taken two or more courses in school law rated the identified barriers to inclusive education higher than those with less formal training in the subject.